PIBID E PRP no contexto do ensino remoto emergencial: análise das práticas pedagógicas em ciências da natureza - Magnoni, Fabio Moda (Universidade Federal de São Carlos, 2025)
This research is set within the context of Emergency Remote Teaching, implemented as an alternative to in-person classes during the COVID-19 pandemic. In this context, the study investigates the pedagogical practices carried out in the area of Natural Sciences, as reported in articles about PIBID (Institutional Program of Teaching Initiation Scholarships) and PRP (Pedagogical Residency Program). The selected database to identify such works was the Capes Periodicals Portal, due to the robustness of its collection. Through pre-established search descriptors, works from different areas were found, which, after filtering, were restricted to the area of Sciences/Biology. After this final filtering, the remaining works included: four related to PIBID and seven related to PRP. Thus, this dissertation is characterized as a bibliographical research, and for data analysis, the Discursive Textual Analysis (DTA) method was adopted, as proposed by Moraes and Galiazzi (2016). The study achieved its proposed objectives, contributing to discussions in the field of Science Education. It was found that the most recurring pedagogical models in the analyzed practices were the Constructivist model and the Science, Technology, and Society (STS) model, according to the framework of Fernandes (2015). Therefore, it was concluded that the lack of technological support for students and teachers, as well as the scarcity of resources in schools, hindered the development of learning in Emergency Remote Teaching, while Information and Communication Technologies (ICTs) proved to be an essential support for the pedagogical practices carried out.
PIBID and PRP in the context of emergency remote teaching: analysis of pedagogical practices in natural sciences
Keywords: Ensino de ciências; Formação de professores; Metodologias de ensino; Biologia; Pandemia; Science education; Teacher training; Teaching methodologies; Biology; Pandemic; OUTROS::CIENCIAS